Validation of the replacement name Eusceliotes Stebbing, 1888 for the pelagic hyperiidean amphipod genus Euscelus Claus, 1879 (Crustacea: Amphipoda: Hyperiidea: Parascelidae), preoccupied by Euscelus Schoenherr, 1833 (Insecta: Coleoptera: Attelabidae) - Zeidler, Wolfgang (Zootaxa, 2017)
The generic name Euscelus was originally proposed by Schoenherr (1833: 205) for a genus of Leaf Rolling weevils (Insecta: Coleoptera: Attelabidae). It is a valid name, in current use, for a relatively large genus of weevils, widespread in northern South America and central America, including the West Indies and the Caribbean (e.g. Hamilton 2007; Legalov 2007). Euscelus Claus, 1879 was established as a monotypic genus of pelagic amphipod (Crustacea: Amphipoda: Hyperiidea: Parascelidae). It is a very rare genus, still monotypic, with the only species, E. robustus Claus, 1879, having been recorded only twice in the literature prior to my review of the families and genera of the superfamily Platysceloidea (Zeidler 2016); initially by Claus (1879), from the Indian Ocean (off Zanzibar), and secondly by Spandl (1927), from the North Atlantic Ocean (off the Azores). Both authors only recorded males. While examining the collections of the Zoological Museum, University of Copenhagen (Zeidler 2016) more specimens of this rare species were located amongst the collections of the Dana expeditions of 1928–1930 (Jespersen & Tåning 1934), thus enabling a more complete description of the species including that of females. It was recently brought to my attention that, according to the data base Interim Register of Marine and Nonmarine Genera (Rees 2016), Euscelus Claus, 1879 is a junior homonym of Euscelus Schoenherr, 1833. While researching this problem I discovered that Stebbing (1888) had also become aware of this homonymy and had suggested the replacement name Eusceliotes. Unfortunately, Stebbing (1888) only refers to the name in his index (pp. 1672, 1699) and hence subsequent authors were unaware of the above homonymy and Stebbing’s replacement name, although it is listed by Neave (1939: 370). The purpose of this communication is to resolve the above homonymy by validating Stebbing’s (1888) replacement name. This action is preferred to proposing yet another new name for Euscelus Claus, 1879, in order to avoid further confusion, because Stebbing’s name, Eusceliotes, already exists in the literature (Stebbing 1888, Neave 1939).